2013
DOI: 10.1103/physrevlett.110.123003
|View full text |Cite
|
Sign up to set email alerts
|

Charge Oscillation Controlled Molecular Excitation

Abstract: The direct manipulation of charge oscillations has emerged as a new perspective in chemical reaction control. Here, we demonstrate, in a joint experimental and theoretical study, that the electron dynamics of a molecule is efficiently steered by controlling the interplay of a driving femtosecond laser pulse with the photoinduced charge oscillation. These oscillations have a typical Bohr period of around 1 fs for valence electrons; therefore, control has to be exerted on a shorter time scale. Specifically, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…In the first case, a wavepacket is launched, and its ensuing (ro-)vibrational dynamics is exploited. In the strong-field regime, the laser pulse coherently controls the dynamics during the pulse while utilizing the effective modification of the energy levels of atoms [201][202][203][204] or, respectively, the potential energy landscape experienced by the molecules, via the dynamic Stark effect [205][206][207].…”
Section: State Of the Artmentioning
confidence: 99%
“…In the first case, a wavepacket is launched, and its ensuing (ro-)vibrational dynamics is exploited. In the strong-field regime, the laser pulse coherently controls the dynamics during the pulse while utilizing the effective modification of the energy levels of atoms [201][202][203][204] or, respectively, the potential energy landscape experienced by the molecules, via the dynamic Stark effect [205][206][207].…”
Section: State Of the Artmentioning
confidence: 99%
“…amplitude of VUV harmonics, it is possible to induce full electromagnetic transparency in He, by destructively interfering two electronic wave packets of the same amplitude and opposite phases (26). Other recent work used shaped intense femtosecond laser pulses to manipulate populations by controlling the oscillating charge distribution in a potassium dimer (27).…”
Section: Significancementioning
confidence: 99%
“…[25] Within that context femtosecond time-resolved photoelectron spectroscopy [26,27] has been used to study nuclear dynamics [26,28] as well as changes in the electronic structure [29] on electronically excited molecular states. Direct control of charge oscillations for molecular excitation [30] as well as the generation and detection of atomic ring currents [31] has been demonstrated. In addition, it has been shown that polarization-shaped laser pulses give access to the vectorial aspects of light-matter interaction [32] and that the momentum distribution of photoelectrons resulting from multiphoton ionization with polarization-shaped laser pulses can be crafted in a sophisticated fashion [33] and detected with the help of tomographic reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%